Arrest of psychological well-being in patients with a chronic-degenerative disease - Boyzo, Blanca Leonor Aranda; Bautista, Francisco Jesús Ochoa; Aranda, Rodrigo Ochoa (Seven Editora, 2023)
The concept of Psychological Well-being arose in the United States and was refined as a result of the development of industrialized societies and interest in living conditions. Initially, feeling good was associated with physical appearance, intelligence or economic aspect, but nowadays, as a result of several researches, it is known that Psychological Well-being is not only related to these variables but also to healthy practices and personal subjectivity. DOI: https://doi.org/10.56238/colleinternhealthscienv1-048